Pearls for Managing Atopic Dermatitis in Patients With Low Socioeconomic Status. Issue 5 (September 2020) - Sachdeva, Muskaan; Price, Kyla N.; Hsiao, Jennifer L.; Shi, Vivian Y.
Abstract : Atopic dermatitis (AD) is a chronic inflammatory dermatosis presenting with inflamed and itchy skin. Recent studies have shown an inverse relationship between socioeconomic status and the severity of AD. Low socioeconomic status (LSES) individuals with AD face specific barriers that may impede management. These include forgoing doctor's appointments due to transportation costs, inability to take time off from work, and lack of affordable childcare services. Unaffordable medications and over-the-counter products for managing AD further present as significant challenges for LSES patients. This article aims to offer practical and affordable recommendations to help mitigate the challenges faced by LSES patients with AD and thereby alleviate disease burden and improve treatment outcomes.